Prevalence of denture induced oral mucosal lesions in removable denture wearers - Muhammad Fatah , Layla; Mahmud Saleh , Mahabad; S. Khalid , Sura; F. Alzubadee , Ali (Diyala Journal of Medicine, 2024)
Background: Dentures can cause pathological problems to the oral tissues known as denture-induced mucosal lesions; the most common type is denture stomatitis. Objective: To estimate the frequency of denture-induced mucosal lesions among denture wearer patients attending oral diagnosis clinic /Faculty of Dentistry in Tishk International University. Patients and Methods: A patient who uses either removable partial or complete dentures was included. The patient’s gender and age, denture-related data, and oral lesions induced by dentures were evaluated. The data were statistically analyzed using chi-square and multivariate logistic regression. Results: Oral lesions (23.5%) were more common in males; the lesions found include denture stomatitis, denture hyperplasia, traumatic ulcers, and angular cheilitis. Denture stomatitis was the most common type (7%). The correlation between vertical dimension state and oral lesions was very highly significant. Conclusion: The major cause of denture-induced mucosal lesions was a change in denture vertical dimension and mostly a reduction in vertical dimension.